An international study of trainee-trained transitions: Introducing the transition-to-trained-doctor (T3D) model. (2nd June 2020) - Gordon, Lisi; Teunissen, Pim W.; Jindal-Snape, Divya; Bates, Joanna; Rees, Charlotte E.; Westerman, Michiel; Sinha, Roona; van Dijk, Anne
Abstract: Background: Throughout their careers, doctors and other healthcare professionals experience numerous transitions. When supporting transitions, opportunities for development and learning should be maximized, while stressors having negative impacts on well-being should be minimized. Building on our international data, this study aimed to develop a conceptual model of the trainee-trained transition (i.e. the significant transitions experienced by doctors as they complete postgraduate training moving from trainee/resident status to medical specialist roles). Methods: Employing Multiple and Multidimensional Transitions (MMT) theory and current conceptualizations of clinical context, this study undertook secondary analysis of 55 interviews with doctors from three countries (Netherlands, Cananda and the UK) undergoing trainee-trained transitions. Results: Through this analysis, the Transition-To-Trained-Doctor (T3D) conceptual model has been developed. This model takes into consideration the multiple contexts and multiple domains in which transitions take place. Discussion: This model is significant in that it has several uses and is applicable across countries: to remind doctors, managers and medical educators of the complexity of transitions; to frame and facilitate supportive conversations; and as a basis to teach about transitions.